Enhancing Supply Chain Synchronisation in the Fast Moving Consumer Goods Industry - Mzavanadze, Neringa; Tolocka, Eligijus (Vilnius University Proceedings, 2024)
In 2021–2022, a decade’s worth of disruptions battered material supply chains, establishing them as a permanent factor. COVID-19 caused labour shortages, rising fertiliser costs altered farming, Europe faced energy crises, USA-China tensions grew, and the Ukraine-Russia war escalated. Extreme weather and policy shifts worsened global supply chains, leading to bare shelves and crippled businesses. Just-in-time delivery failed, and traditional supply chains no longer ensure business continuity. This article aims to prove the inefficiencies of traditional supply chains and offer an approach to creating an end-to-end model with better visibility, service, and cost control for Fast-Moving Consumer Goods (FMCG) manufacturing plants. During the research phase, 12 European Pet food production plants were visited, analysing their supply chains via People/Systems/Process lenses. Risks, synchronisation needs, system requirements and training gaps were identified. Preliminary research findings are presented in this article.
Keywords: supply chain disruption; manufacturing,; fast-moving consumer goods; continuous improvement